Comparing the Clinical Severity of Disease Caused by Enteroviruses and Human Parechoviruses in Neonates and Infants. Issue 2 (February 2019) - Black, Sally; Bradley, Carina; Lai, Florence Y.; Shenoy, Savitha; Bandi, Srini; Allen, David J.; Tang, Julian W.
Abstract : Comparison of children hospitalized with enterovirus or human parechovirus (HPeV) detected in their cerebrospinal fluid revealed that HPeV infections presented with more persistent fever, irritability and feeding problems, more frequent leukopenia and lymphopenia and higher admission rates to high dependency or intensive care units. Few HPeV cases were followed up, further studies on long-term outcomes are needed. Abstract : Supplemental Digital Content is available in the text.